PENINGKATAN KINERJA GURU MELALUI PENGUATAN KEPUASAN KERJA DAN KERJA TIM MENGGUNAKAN ANALISIS PATH PADA GURU DI YAYASAN HAJI MUHAMMAD AMIN KECAMATAN PAMIJAHAN KABUPATEN BOGOR - Sahadah, Mutia; Ihsan, Muzhir; Trimulyo, Joko (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2023)
Teacher performance is the work obtained by a teacher who contributes to an institution where he works to achieve the goals of the school's vision and mission. Where the author takes a survey method with a causal approach, this is a method to measure the extent and how much the three variables chosen by the author have a causal relationship with a phenomenon. When the results from the causal approach survey have been obtained, the results will be further analyzed using path analysis. The population chosen by the author is the teacher at the Haji Muhammad Amin Foundation as many as 98 people and the sample is 79 people with a simple random sampling. After doing the path analysis test in the SPSS version 20 application and producing an output. Path analysis testing can be seen from the Coefficients table, it is known that the value of β = 0.537 and 0.211 and score thitung = 5.079 and 1.997 > ttabel 1.66462 at the level of relevance α = 0.05. Therefore, H0 is rejected and H1 is accepted. Thus, it is stated that job satisfaction and teamwork have a direct positive effect on teacher performance.